PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIIC SMP NEGERI 1 PANGKALAN KERINCI - Rahmi, Nur Rahmi; Murni, Atma Murni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The form of this research is collaborative classroom action research and aims to improve mathematics learning outcomes with applied the Cooperative Learning Type Numbered Heads Together (NHT). The subject of the research is students of class VIIIC SMP Negeri 1 Pangkalan Kerinci in the second semester academic year 2013/2014 there are 36 students in the class, consist of 17 boys and 19 girls who have heterogeneous academic ability. The research consist of two cycles and each cycle has four stages, they are planning, implementation, observation, and reflection. The data collected in this research is data on the implementation of the learning process and data on studentâs mathematics learning outcomes. The technique used to collect data on the implementation of the learning process are observation technique, technique of performance appraisal and assessment technique written test. While The technique used to collect data on studentâs mathematics learning outcomes is technique written test in the form of daily test. Analysis technique used to analyze the data in this research is descriptive statistical. Criteria for success of the action in this research is an increas in studentâs mathematics learning outcomes after done action, that the number of student who achieve a score of minimum mastery criteria (MMC) at daily tests I more than student who achieve a score of MMC at basis score and the number of student who achieve a score of MMC at daily tests II more than student who achieve a score of MMC at daily tests I. The number of students who achieve a score of MMC on basic score, daily test I and daily test II are respectively 3%, 14%, and 48%. The learning process during the action given and MMC attainment percentage indicates that the cooperative learning type NHT can improve students mathematics learning outcomes class VIIIC SMP Negeri 1 Pangkalan Kerinci. Key words: Mathematics learning outcomes, Cooperative learning, Numbered Heads Together, Classroom action research.